Multi-angle analysis of Mo on martensite–austenite component and toughness in SCGHAZ of X80 pipeline automatic ring welding - Yuan Li; Qingshan Feng; Haidong Jia; Shaohua Cui; Lianshuang Dai; Huibin Wu; Qingyou Liu; Hesong Zhang; Shujun Jia (Journal of Materials Research and Technology)
In order to solve the embrittlement problem of welded joint of pipeline steel, this paper proposes to study the influence of Mo on M-A component of the subcritically reheated coarse-grained HAZ (SCGHAZ), and Mo on bainite transformation. Through the welding thermal simulation experiment, two kinds of X80 pipeline steel with different Mo content were set different secondary thermal cycle peak temperatures to simulate the heat affected zone (HAZ). Samples in the SCGHAZ were selected to observe the microstructure, M-A component, microalloy-element distribution and fracture crack trend, and comprehensively analyze the reasons for the deterioration of impact toughness caused by the changes of Mo content. The results show that the increase of Mo content leads to the formation of twinning martensite, which is one of the reasons for the deterioration of toughness. Mo is enriched at the interface of ferrite and M-A component, reducing the binding energy at the interface, resulting in the desorption of M-A component from the matrix, the formation of pores and becoming the nucleation site of cracks, resulting in the generation of micro-cracks and the decrease of toughness.